Exploring Students’ Perceptions of the Summary Method as a Reading Comprehension Strategy in Japanese Language Learning - Nur Mustika Indah Permatasari; Febi Ariani Saragih (Chi e Journal of Japanese Learning and Teaching, 2025)
This study investigates students’ perceptions of implementing the summary method in the Advanced Reading 2 course of the Japanese Language Education Study Program at Brawijaya University. Conventional reading classes generally emphasize reading aloud and translating, which often leads students to focus on literal translation rather than comprehension (Trahutami, 2017). To overcome this limitation, the summary method was introduced to integrate reading, writing, and speaking skills, encouraging active language use during lessons. The study employed a descriptive qualitative approach with a case study design involving eight purposively selected students. Data were collected through questionnaires, interviews, and documentation. The findings show that most students viewed the summary method positively, noting that it improved their understanding of reading texts and enhanced their language proficiency. However, students with moderate and lower academic performance experienced difficulties simplifying sentences due to limited vocabulary and grammatical knowledge. Overall, the summary method proved effective in fostering comprehension and promoting language integration. Future research is recommended to include participants from different educational levels to provide broader insights into the method’s implementation in reading instruction.